Influence of Sustainability Reporting on Financial Performance of Corporate Firms Listed on the Nairobi Securities Exchange - Ouma, Hezekiah Adwar; Nyamita, Micah Odhiambo; Keta, Midida Peter (EuroEconomica, 2025)
Sustainability reporting has gained global attention among firms, researchers, and academicians. However, a notable gap remains in empirical literature regarding its specific influence on corporate financial performance, particularly in Kenya. Despite advocacy from the Kenyan Government, sustainability reporting programs among listed corporate firms in Kenya have been slow, with only 46% of the 65 listed firms integrating ESG disclosure into their annual reports by December 2022. Given these gaps, this study examined the influence of sustainability reporting on financial performance among corporate firms listed on the Nairobi Securities Exchange by assessing how each sustainability reporting variable influence Corporate financial performance. Guided by the stakeholder theory, the study employed panel data methodology. A census was conducted on 57 firms, constituting target population between 2014-2023. Findings revealed that environmental reporting positively influenced ROE (β = 0.2091, p < 0.001). Social reporting had the strongest positive effect (β = 0.5880, p < 0.001). Governance reporting showed a moderate positive but statistically insignificant impact (β = 0.0397, p = 0.162). Stakeholder engagement reporting positively correlated with financial performance (β = 0.0917, p < 0.001). Based on these findings, firms should focus on improving environmental, social, and governance reporting to boost financial performance.